Dynamic branch prediction and control speculation. (20th April 2007) - Silc, Jurij; Ungerer, Theo; Robic, Borut
Branch prediction schemes have become an integral part of today's superscalar processors. They are one of the key issues in enhancing the performance of processors. Pipeline stalls due to conditional branches are one of the most significant impediments to realise the performance potential of superscalar processors. Many schemes for branch prediction that can effectively and accurately predict the outcome of branch instructions have been proposed. In this paper, an overview of some dynamic branch prediction schemes for superscalar processors are presented.